Pengaruh Customer Experiences Terhadap Customer Loyalty: (Studi Pada Tamu Meeting di Hotel Pangeran City Padang) - Ryegi Anandia; Youmil Abrian (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research is motivated by one of the substitute hotels of the Pangeran Group, namely the Pangeran City Padang Hotel, which is still considered good among 3 star hotels. The aim of this research is to analyze the extent to which customer experience influences customer loyalty at the Pangeran City Padang Hotel. This research uses an Associative Causal type with a cause and effect approach or relationship because it uses quantitative methods. Data was obtained from distributing surveys to research respondents. The Customer experience variable obtained an average result of 66.33 with a range of 63 - 75 categorized as very good, the Customer loyalty variable obtained an average result of 38.16 with a range of 37.8 - 45 categorized as very good. with a sample mean value of 0.581, the t-statistic value of 4.213 is greater than 1.96 and the p value of 0.000 is less than 0.05, so it can be said that the Customer experience variable has a significant positive effect on the Customer loyalty variable. So the hypothesis accepted in this research is Ha while the hypothesis Ho is rejected, it can be concluded that where there is an increase in good customers it will increase customer loyalty to return to the Pangeran City Padang Hotel.